PARADIGM-HF: Rationale and Design - Nichols, Emma Hitt (MD Conference Express, 2014)
The Multicenter, Randomized, Double-blind, Parallel Group, Active-controlled Study to Evaluate the Efficacy and Safety of LCZ696 Compared to Enalapril on Morbidity and Mortality of Patients With Chronic Heart Failure and Reduced Ejection Fraction [PARADIGM-HF; NCT01035255] is the largest trial ever conducted with patients with heart failure with a reduced left ventricular ejection fraction and was designed to replace the current standard of care. This article discusses the rationale and design of the PARADIGM-HF trial.